2020
DOI: 10.3390/nano10061162
|View full text |Cite
|
Sign up to set email alerts
|

Gas Sensing Performance and Mechanism of CuO(p)-WO3(n) Composites to H2S Gas

Abstract: In this work, the compositional optimization in copper oxide/tungsten trioxide (CuO/WO3) composites was systematically studied for hydrogen sulfide (H2S) sensing. The response of CuO/WO3 composites changes from p-type to n-type as the CuO content decreases. Furthermore, the p-type response weakens while the n-type response strengthens as the Cu/W molar ratio decreases from 1:0 to 1:10. The optimal Cu/W molar ratio is 1:10, at which the sensor presents the ultrahigh n-type response of 1.19 × 105 to 20 ppm H2S g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…These materials are also inexpensive and environmentally benign. , Cu 2 O (bandgap 1.9–2.6 eV), a natural p-type semiconductor, has extensively been studied for its excitonic behavior, but interest has recently shifted to potential solar cell applications . CuO (bandgap 0.8–1.8 eV), also a p-type semiconductor, has shown promise in catalytic, gas sensing, and magnetic applications. By varying deposition conditions, the bandgaps for Cu 2 O and CuO can be tuned from 1.2 to 2.6 eV, making them versatile materials for solar absorption in photovoltaic devices. , In addition, due to favorable band edge misalignment that places the CuO valence band and conduction band lower than those of Cu 2 O and the potential charge separation mechanism, heterostructured Cu 2 O/CuO thin films or nanostructures have been proven to have better photocatalytic performance compared to Cu 2 O or CuO single-component materials. For example, Jiang et al reported on CuO/Cu 2 O nanowires with methyl orange (MO) degradation rates 260 times higher than pure Cu 2 O .…”
Section: Introductionmentioning
confidence: 99%
“…These materials are also inexpensive and environmentally benign. , Cu 2 O (bandgap 1.9–2.6 eV), a natural p-type semiconductor, has extensively been studied for its excitonic behavior, but interest has recently shifted to potential solar cell applications . CuO (bandgap 0.8–1.8 eV), also a p-type semiconductor, has shown promise in catalytic, gas sensing, and magnetic applications. By varying deposition conditions, the bandgaps for Cu 2 O and CuO can be tuned from 1.2 to 2.6 eV, making them versatile materials for solar absorption in photovoltaic devices. , In addition, due to favorable band edge misalignment that places the CuO valence band and conduction band lower than those of Cu 2 O and the potential charge separation mechanism, heterostructured Cu 2 O/CuO thin films or nanostructures have been proven to have better photocatalytic performance compared to Cu 2 O or CuO single-component materials. For example, Jiang et al reported on CuO/Cu 2 O nanowires with methyl orange (MO) degradation rates 260 times higher than pure Cu 2 O .…”
Section: Introductionmentioning
confidence: 99%
“…Long-term stability is another important indicator of gas sensors. 38,54 Figure 6a presented the repeatability to 5 ppm HCHO over a period of 15 consecutive days. The response values fluctuated slightly over time, but the range of fluctuation was slight and the fluctuation ratio was only approximately 10%.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, no additional impurity peaks were detected in the XRD analysis, suggesting chemical compatibility among all components. 24 The chemical states of elements (W, Ti, and O) in the WO 3 , TW and Pt@TW-2 samples were analyzed using X-ray photoelectron spectroscopy (XPS), as shown in Fig. 4 and ESI Fig.…”
Section: Sample Characterizationmentioning
confidence: 99%